The influence of microstructural characteristics on the mechanical properties of Ti6Al4V alloy produced by the powder metallurgy technique - IVANA CVIJOVIC; MIROLJUB VILOTIJEVIC; MILAN T. JOVANOVIC (Journal of the Serbian Chemical Society, 2006)
The influence of hot-pressing (HP-ing) parameters on the microstructure, tensile properties and impact toughness of Ti6Al4V alloy produced by the powder metallurgy (PM) technique was evaluated. The experimental results show that variations in the microstructural morphology and residual porosity play an important role in affecting the mechanical properties of this alloy. The lamellar microstructure with a higher density, obtained by HP-ing above the b-transition temperature (Tb), was found to exibit a higher tensile strenght and toughness than the globular microstructure produced below Tb. Although both types of microstructure show a mixed fracture, the ductile mode was more pronounced in the case of the fully lamellar microstructure. By controlling the HP-ing pressure and duration time, the globular microstructure, with lower porosity, improved tensile strength and ductility in combination with a better resistance to crack initation and propagation, can be obtained.